Non-Cardiogenic Thromboembolism in a Persian Cat with Hypertrophic Cardiomyopathy - Fontoura Mateus, Nathália Lopes; Velozo Leal, Paula; Candolo Marques, Beatriz; da Silva, Karen Fernanda; Mattei, Douglas Rodrigo; Carvalho, Elizabeth Regina (Acta Scientiae Veterinariae, 2020)
Background: Hypertrophic cardiomyopathy is the most common acquired cardiovascular disease in the feline species. A frequent complication of this cardiomyopathy is the development of cardiac congestive failure, left atrial enlargement and subsequent development of arterial thromboembolism. In a significant percentage of affected animals there is progression to congestive heart failure, resulting in cyanosis and dyspnea, often the first clinical signs reported by owners. This is a report of a 10-year-old Persian cat with hypertrophic cardiomyopathy and venous and arterial thromboembolism of non-cardiogenic origin. Case: The patient was referred for cardiac evaluation, arterial thromboembolism was the suspected cause of tetraparesis. On clinical examination, a metacarpal pulse was present in all limbs; there was no cyanosis or peripheral hypothermia thus, ruling out a thromboembolic event in the limbs. Changes consistent with feline asthma and pulmonary edema were seen on radiographs, therefore hypertrophic cardiomyopathy was suspected. Treatment with enalapril (0.25 mg/kg every 12 h) for the heart condition and prednisolone (1 mg/kg every 24 h) for asthma was started. Nine days later, the patient developed mixed dyspnea (inspiratory and expiratory) and was hospitalized with signs consistent with arterial thromboembolism: paralysis and cold extremities in the right and left pelvic limbs. The patient was euthanized due to the poor prognosis. Post mortem and histopathological findings revealed left ventricular concentric hypertrophy, with no valvular changes; disseminated intravascular coagulation, with thrombi in the arterial (iliac arteries, pancreatic and renal vessels) and venous (pulmonary and renal veins) beds; as well as multiple neoplastic lung masses, identified as scirrhous pulmonary adenocarcinoma, responsible for increased interstitial radiopacity. Metastasis was also identified at the tracheal bifurcation, causing radiographic changes similar to the alveolar pattern of pulmonary edema. Discussion: The origin of the concentric left ventricular hypertrophy was not established. Both primary hypertrophy, due to breed-related genetic predisposition or secondary hypertrophy, due to systemic hypertension from chronic kidney disease are possibilities. However, despite the left ventricular concentric hypertrophy and the presence of thrombus under the mitral valve, it was not thought that the patient had cardiogenic thromboembolism, since this would not explain the venous thrombi. The arterial and venous thromboembolism in this case were the result of paraneoplastic syndrome due to pulmonary adenocarcinoma, which was a triggering factor for disseminated intravascular coagulation and multiple thrombus formation, both in arterial and venous beds. Tumor cells may promote direct and indirect modifications in the coagulation cascade and, thus hypercoagulability. The hypercoagulatory state promoted by the tumor associated with the Virchow triad seen in feline species, explains the occurrence of thrombosis in this case report. Sensitive imaging tests, such as computed tomography or magnetic resonance imaging, may be required in middle-aged cats with hypertrophic cardiomyopathy and clinical presentations of thromboembolism or respiratory signs, in order to exclude pulmonary neoplasm as a differential diagnosis for thrombus formation and dyspnea. Furthermore, it is speculated that the antitumor effect of heparin used in the treatment for arterial thromboembolism may delay the diagnosis of lung neoplasia in cats.